Enzyme-mediated production of sugars from sago starch: statistical process optimization - Wee, L.L.; Annuar, M.S.M.; Ibrahim, Shaliza; Chisti, Y. (Taylor & Francis, 2011)
Glucoamylase (γ-amylase, EC 3.2.1.3) from Aspergillus niger was used to hydrolyze the soluble sago starch to reducing sugars without any major pretreatment of the substrate. A 2 L stirred tank reactor was used for the hydrolysis. The effects of pH, temperature, agitation speed, substrate concentration, and enzyme concentration on the reaction were investigated in order to maximize both the initial reaction velocity v and the final product yield Y p/s. A response surface methodology central composite design was used for the optimization. A maximum Y p/s of 0.58 g · g -1 and a high v of 0.50 mmoles ·L -1 · min -1 were predicted by the response surface at the identified optimal conditions (61°C, a substrate concentration of 0.1 (w/v, g/=100 mL), an enzyme concentration of 0.2U·mL -1). The pH and agitation speed did not significantly affect the production of sugars. The subsequent validation experiments under the above-specified optimal conditions confirmed a maximum conversion rate and yield combination of 0.51±0.07 mmoles ·L -1 · min -1 and 0.60±0.08 g · g -1. © Taylor & Francis Group, LLC.